Establishment of Mycorrhizas of Four Different Species of Arbuscular Mycorrhizal Fungi Observed Using Petri-Dish Microcosm - IRDIKA MANSUR; JOHN DODD; PETER JEFFRIES (Microbiology Indonesia, 2010)
The Petri-dish microcosm is a simple system to study the development of arbuscular mycorrhizal fungi (AMF) and has been shown to be suitable to observe the establishment of Acaulospora tuberculata BEG41, Gigaspora rosea BEG111, Glomus manihotis BEG112 and Scutellospora heterogama BEG40 on plant root. The non-agar based system could be easily used to observe the whole course of development of fungal-root interactions as well as the extra-radical structures of AMF without destructive sampling. It was found that these AMF species were unique with regard to spore germination, root colonization, the architecture of the extra-radical mycelium (ERM), the spread of the ERM in the media, and sporulation. The ERM of A. tuberculata BEG41and G. manihotis BEG112 spread mainly close to the root system, while the ERM of G. rosea BEG111 and S. heterogama BEG40 could occupy areas unoccupied by roots. The unique structure, the branch absorbing structure, was found in the four species of AMF, but differed in their shape and size